2019
DOI: 10.1177/1533033819857737
|View full text |Cite
|
Sign up to set email alerts
|

IL-9 Exerts Antitumor Effects in Colon Cancer and Transforms the Tumor Microenvironment In Vivo

Abstract: As a newly discovered cytokine, interleukin 9 was initially considered a T-lymphocyte growth factor. Interleukin 9 affects target cells by binding to a member of the γc-family of receptors and is involved in inflammation, autoimmune diseases, and other ailments. In recent years, mounting evidence reveals that interleukin 9 exerts antitumor effects, which has attracted considerable attention. Many previous studies were performed in vivo by establishing a mouse model of melanoma. Here, interleukin 9 protein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 46 publications
1
26
3
Order By: Relevance
“…However, in line with our results, high levels of IL-2 in CRC patients was observed 430 also by Bosek et al 104 . Regarding IL-9, contrary to our result, Wang et al shown that IL -9 was less 431 expressed in human colon carcinoma 105 . However, even Huang et al reported low amounts of IL-9 432 in tissue and plasma of CRC patients but these low levels were associated with tumor progression 106 .…”
Section: Statistical Analysis Of the Association Between Tissue Microcontrasting
confidence: 99%
“…However, in line with our results, high levels of IL-2 in CRC patients was observed 430 also by Bosek et al 104 . Regarding IL-9, contrary to our result, Wang et al shown that IL -9 was less 431 expressed in human colon carcinoma 105 . However, even Huang et al reported low amounts of IL-9 432 in tissue and plasma of CRC patients but these low levels were associated with tumor progression 106 .…”
Section: Statistical Analysis Of the Association Between Tissue Microcontrasting
confidence: 99%
“…However, no substantial differences in tumor growth retardation and body weight change was observed between the treatments with targeted F8IL9F8 and the untargeted variant KSFIL9KSF (based on the irrelevant anti-hen egg lysozyme antibody KSF) ( Figure 3A). The CT26 model, recently described as an immunologically "hot" tumor [40], was investigated due to earlier reports demonstrating in vivo growth impairment of CT26 tumors ectopically expressing IL9 [14,15]. In order to investigate dose dependence effect of IL9 therapy, mice received three injections of F8IL9F8 at different doses, i.e.…”
Section: Radiolabeled Biodistribution and Tumor Therapiesmentioning
confidence: 99%
“…They found that the expression levels of IL-9 protein and messenger RNA were lower than those in the controls and correlated with TNM staging, Dukes staging, lymph node metastasis, and good prognosis. In vivo , IL-9 overexpression significantly inhibited tumor growth and resulted in a longer survival time in a mouse subcutaneous allograft model (80). Moreover, an ectopically expressed membrane-bound form of IL-9 induces an immunostimulatory effect that suppresses the growth of CT26 colon cancer cells (81).…”
Section: The Role Of Th9/il-9 Th17/il-17 and Th22/il-22 In The Devementioning
confidence: 99%